Effect of geometrical and temperature-dependence parameters on forced convection of a nanofluid in a micro-channel heat sink - Nebbati, Rabah; Kadja, Mahfoud (World journal of engineering, 2016)
PurposeThe purpose of this study is the numerical prediction of the thermal and hydraulic characteristics (Nusselt number and shear stress) of a forced convection laminar flow through a rectangular micro-channel heat sink, using constant and temperature-dependent thermo-physical properties. The effects of the solids volume fraction and the size of the micro-channel on heat transfer enhancement have also been investigated.Design/methodology/approachThe authors use the flow of a water-Al2O3 nanofluid and a single-phase approach. The equations are solved using the commercial code Fluent Version 6.3. This code uses the finite volume approach to solve the equations subject to the boundary conditions, which govern three-dimensional conjugate convection-conduction heat transfer model. The physical domain was meshed using the code GAMBIT. The mesh used is non-uniform and was obtained by sweeping in the Z direction an X-Y surface meshed with QUAD/pave type cells.FindingsThe results clearly show that the inclusion of nanoparticles produces a considerable increase in the heat transfer. Also, the temperature-dependent models present higher values of local and average Nusselt number than in the case of constant thermo-physical properties, and an increase in the channel dimensions leads to an important increase in heat transfer. Consequently, we ensure a better cooling of the base of the micro-channel heat sink.Research limitations/implicationsBecause of the settling of nanoparticles, the research results may not be generalized to high values of solids volume fraction. Therefore, researchers are encouraged to find other techniques of cooling when the heat loads exceed values that cannot be dissipated using nanonofluids.Practical implicationsThe paper includes implications for the miniaturization of electronic devices such as in microprocessors or those used in robotics and automotive industries, where continually increasing power densities are requiring more innovative techniques of heat dissipation from a small area and small coolant requirements.Originality/valueThis paper shows the implementation of variable property nanofluid models in CFD commercial codes.